Cadastre In Nepal: Past and Present - Adhikary, Krishna Raj; Paudyal, Dev Raj; Joshi, Prakash (Journal on Geoinformatics, Nepal, 2007)
The history of land recording system is very old in Nepal. Though, the administration of land was mentioned in ancient history, it became institutionalized since Lichhabi era. There was the provision of village panchali for the administration and management of land at village level. Many improvements like classification of lands, specification for land measurements, provision measurement units (as hale, pate, kute, kodale etc.), development of special profession for land survey and measurement (Dangol), land adjudication and boundary description of land etc. were made during Malla era. Later, the cadastral maps were also realized as an important component for land administration. The chain survey method was introduced to prepare cadastral maps. Systemic Cadastral Survey was started after the land reform programme in 2021 B.S. In the beginning, the cadastral survey was done in free sheet connecting with local points. 38 out of 75 districts were surveyed on local base point where as 37 districts were surveyed with the control points connected to the National geodetic network. The primary focus of cadastral surveying was fiscal purpose to generate revenue from land tax. Later, the legal cadastre system was developed as it provides more land tenure security to the land owners. Now the concept of multi-purpose cadastre is emerging. There are nine Survey Goswaras & a Survey office under Cadastral Survey Branch for cadastral surveying of different districts. Digital technology has been introduced for re-cadastral mapping from 2062 B.S. in Banepa Municipality. In this paper an attempt has made to review the cadastral system of Nepal from historical perspectives. This paper starts with introduction and describes about the historical context of land recording and cadastral surveying in Nepal. It then elaborates the institutions involved for the cadastral surveying in Nepal. The future vision of cadastral system is also described in this paper. Finally, it concludes with some concluding remarks.